Time-dependent changes in stepping performance and velocity following partial dopaminergic lesions in the SNc of male and female rats - Diego Lievano Parra; Juan David Garavito Coronado; Greg Jensen; Valeria Gonzalez Diaz; Fernando Cardenas Parra (PLoS ONE, 2026)
Parkinson’s disease (PD) is a neurodegenerative disorder in which gait disturbances are a major source of disability, yet their early manifestations remain difficult to characterize because prodromal PD is challenging to identify in humans. Rodent models may help address this gap by approximating partial dopaminergic loss and enabling investigation of motor changes that precede overt symptoms. Here, we examined stepping performance and velocity in Wistar rats following unilateral low-dose 6-hydroxydopamine (6-OHDA) lesions in the substantia nigra pars compacta (SNc). Animals were assessed weekly for six weeks in the horizontal ladder, where velocity and footfall errors were quantified using markerless pose estimation with DeepLabCut (DLC). Lesioned animals showed greater tyrosine hydroxylase (TH) asymmetry than controls, accompanied by persistent but gradually attenuating impairments in stepping accuracy. Footfall errors peaked around week three and remained elevated thereafter, whereas velocity showed more heterogeneous changes across time. Although sex effects were not uniformly robust, control females showed an increase in velocity across weeks, whereas lesioned females exhibited a less pronounced and more variable pattern. These findings indicate that partial SNc lesions can reveal subtle and time-dependent alterations in locomotor skills relevant to the study of early dopaminergic dysfunction. Combined with DLC-based tracking, this framework provides a practical approach for detecting early behavioral changes and refining the study of preclinical motor features of PD.